NATURAL LANGUAGE UNDERSTANDING WITH PYTHON combine natural language technology, deep learning, and large language models to create human-like language comprehension in computer systems - Dahl, Deborah Anna (PACKT PUBLISHING LIMITED, 2023)
Unleash the full potential of natural language understanding (NLU) and create impeccable systems by mastering the art of data acquisition and technology selection Purchase of the print or Kindle book includes a free PDF eBook Key Features Master NLU concepts from basic text processing to advanced deep learning techniques Explore practical NLU applications like chatbots, sentiment analysis, and language translation Gain a deeper understanding of large language models like ChatGPT Book Description Natural Language Understanding facilitates the organization and structuring of language allowing computer systems to effectively process textual information for various practical applications. Natural Language Understanding with Python will help you explore practical techniques for harnessing NLU to create diverse applications. Complete with step-by-step explanations of essential concepts and practical examples, you'll begin by learning about NLU and its applications. You'll then explore a wide range of current NLU techniques and their most appropriate use-case. In the process, you'll be introduced to the most useful Python NLU libraries. Not only will you learn the basics of NLU, you'll also discover practical issues such as acquiring data, evaluating systems, and deploying NLU applications along with their solutions. The book is a comprehensive guide that'll help you explore techniques and resources that can be used for different applications in the future. By the end of this book, you'll be well-versed with the concepts of natural language understanding, deep learning, and large language models (LLMs) for building various AI-based applications. What you will learn Explore the uses and applications of different NLP techniques Understand practical data acquisition and system evaluation workflows Build cutting-edge and practical NLP applications to solve problems Master NLP development from selecting an application to deployment Optimize NLP application maintenance after deployment Build a strong foundation in neural networks and deep learning for NLU Who this book is for This book is for python developers, computational linguists, linguists, data scientists, NLP developers, conversational AI developers, and students looking to learn about natural language understanding (NLU) and applying natural language processing (NLP) technology to real problems. Anyone interested in addressing natural language problems will find this book useful. Working knowledge in Python is a must.